Vitalism and the Scientific Image in Post-Enlightenment Life Science, 1800-2010
VI, 377 p. 5 illus.
Keywords: Vitalism is understood as impacting the history of the life sciences, medicine and philosophy, representing an epistemological challenge to the dominance of mechanism over the last 200 years, and partly revived with organicism in early theoretical biology. The contributions in this volume portray the history of vitalism from the end of the Enlightenment to the modern day, suggesting some reassessment of what it means both historically and conceptually. As such it includes a wide range of material, employing both historical and philosophical methodologies, and it is divided fairly evenly between 19th and 20th century historical treatments and more contemporary analysis. This volume presents a significant contribution to the current literature in the history and philosophy of science and the history of medicine.